THE ROLE OF GAMES IN TEACHING FOREIGN LANGUAGES - Otabekova Mashhura Otabekovna; Abdullaeva Lola Tohirovna (Bright Mind Publishing, 2025)
The integration of games into language teaching has gained prominence in recent years, reflecting a broader shift towards learner-centered, engaging, and dynamic educational strategies. This article explores the role of games in foreign language acquisition, examining their educational benefits, types of games suitable for language learning, and how they can be implemented in diverse classroom settings. Drawing upon existing research and practical examples, the article demonstrates how games promote active learning, enhance motivation, foster social interaction, and facilitate the acquisition of linguistic and cultural knowledge. It concludes by highlighting the challenges and limitations of using games in language teaching and suggesting strategies for overcoming them to maximize the effectiveness of this approach.
Keywords: Language Learning, Educational Games, Foreign Languages, Active Learning, Motivation, Interaction, Classroom Techniques, Language Acquisition, Game-Based Learning.